Keterpaduan System Peradilan Pidana Anak (Integrated Juvenile Justice System) Dalam Penerapan Diversi Terhadap Anak Pelaku Tindak Pidana - Faiz Ahmed Illovi; Marlina Marlina; Mahmud Mulyadi; Jelly Leviza (USU LAW JOURNAL, 2019)
Abstract.Criminal Justice System Children should not be construed as a judicial body as stipulated in Article 24 paragraph (2) of the Constitution of the Republic of Indonesia Year 1945, which stated that the judicial power is done by a Supreme Court and judicial bodies underneath it in the public courts, religious courts, military courts, administrative courts and by a Constitutional Court. In accordance with the above background, then some of the things that are at issue in this study is as follows: What is the rule of law on coordination between the sub-systems of criminal justice in the application of diversion, How coordination sub criminal justice system in the application of diversion to criminal child and what policies implemented by the sub-system of juvenile justice in the application of diversion. Normative juridical research method is useful to know or to know whether and how the law has on a particular issue and also can explain or explain to others whether and how the law regarding a particular event or issue. In using normative legal research in this thesis will be focused on normative legal research is qualitative. The conclusion of this thesis, Making rule of  law how coordination between sub criminal justice system in the application of diversion, according to the provisions of Article 7 of Law SPPA, diversion can only be carried out to the children who were threatened with imprisonment under seven (7) years and is not a repetition of criminal acts (residive). Making Sub Criminal Justice system Coordination in the application of criminal diversion of the child, the legal protection of children in judicial proceedings conducted since the beginning level of inquiry, investigation, prosecution, examination before the court until the execution of the court's ruling and during the judicial process, the rights of the child shall be protected by law and therefore must be done consistently by the parties concerned with solving the naughty child. Policies implemented by sub-system of juvenile justice in the application of diversion, Diversi shall be made on the level of investigation, prosecution and court examination of the child in court, although the consequences of "compulsory" at the insistence of diversion also become blurred because of the sanctions against the waiver of this provision, which is set at article 96 has been declared contrary to the Constitution of 1945 and does not have binding legal force by the Constitutional Court Decision Number 110 / PUU-X / 2012.   Keywords: juvenile, criminal, child,